Crosstalk: keratinocytes and immune cells in psoriasis - Kamata, Masahiro; Tada, Yayoi (Frontiers in Immunology, 2023)
In the past, psoriasisPsoriasis was considered to be a skin disease caused only by keratinocyte disordersdisorders of keratinocytes in the past. However, reports of psoriasis successfully treated with cyclosporine altered our understandings for the pathogenesis of psoriasis. In addition, the efficacy of immunosuppressive drugs and biologics used to treat for psoriasis proves that psoriasis is one ofan immune-mediated diseases. To date, a lot of studies were conducted, and they revealed that a Indeed, a variety of immune cells are involved in the pathogenesis of psoriasis, including dendritic cells, Th17 cells, and resident memory T cells. , Furthermore, keratinocytes play a role in the development of psoriasis as immune cells by secreting antibacterial peptides, chemokines, tumor necrosis factor-α, interleukin (IL)-36, and IL-23. These immune cells and skin cells interact and drive the aberrant differentiation and proliferation of keratinocytes. including dendritic cells, Th17 cells, resident memory T cells, type 3 innate lymphoid cells, etc. Furthermore, keratinocytes themselves play a role in the development of psoriasis as immune cells.Those immune cells and skin cells interact with one another, consequently driving aberrant differentiation and proliferation of keratinocytes. In this review article, we focus on this This crosstalk between keratinocytes and immune cells and discuss its importance critical in the pathogenesis of psoriasis forms an inflammatory loop, resulting in the persistence or exacerbation of psoriasis plaques..